Gambaran Dimensi Internal Dalam Konsep Diri Anak Asuh UPTD Kampung Anak Negeri Surabaya - Greisca Rosa Shafira (Poltekkes Kemenkes Surabaya, 2017)
Every children have rights to survival, growth, development and to protected from violence and discrimination. Family’s problem such as poverty, bad relationship between children and parents, divorce, and acts of violence in children that can cause children become street children and abandoned children. Health as a prosperous condition of the physical, mental and social conditions that eneble everyone to live productively both socially and economically. Productive living can be achieved by freely from physical, mental and social disturbances. Mental health is the ability of a person to be able to adjust to himself, others, society and environment. The form of mental disorders can be a sense of inferiority, anxiety, and lethargy without known cause is a mental disorder that is often experienced by children so that can effect the learning process. Self-concept as the most basic psychological unit is used to understand the mental processes of individual. The research was conducted at UPTD Kampung Anak Negeri Surabaya with descriptive method of qualitative approach. Instrument in this research is guidance of interview and observation with informant amounted to 8 people. Retrieval of informant use purposive sampling technique. Factors in internal dimensions of the children are shown in behavioral self and judging self. Street and abandon children feel satisfied with him now compared with the first before being in UPTD Kampung Anak Negeri. Children with abandoned children and street children backgrounds able to achieve and actualize themselves after getting assisted in UPTD Kampung Anak Negeri.